THE INFLUENCE OF SELF-ESTEEM ON THE EMOTIONAL STATE OF AN ATHLETE AS PERSONALITY - Vysochina N. (Kharkov National Pedagogical University, 2010)
Annotation. Studies and analyses the influence of psychological factors on the emotional state of an athlete as personality. Scientific literature elucidates poorly the impact of self-esteem on the emotional state of an athlete as a factor promoting optimization of professional activity, which has made this problem very interesting for the study. The aim of this study is to trace the relationship between the self-esteem level and emotional state of an athlete personality as a factor promoting optimization of professional activity. The following methods were used: theoretical analysis, compilation and systematization of data from scientific literature. Research shows that the level of self-esteem exerts direct effect on the emotional state of an athlete, which predetermines his professional results.